As written, the expression (x + 3)(x + 9) is not an equation, so there is nothing to solve. This expression may be simplified by multiplying through the parenthesis.

(x + 3)(x + 9) = (x + 3)*x + (x + 3)*9

= x^2 + 3x + 9x + 3*9

= x^2 + 12x + 27

Often expressions such as that given are set equal to zero, in which case there is an equation.

(x + 3)(x + 9) = 0 may be solved by remembering that if a*b = 0, then either a or b must be equal to zero. Thus either x + 3 = 0 or x + 9 = 0, meaning that x = -3 or x = -9

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.